Impact of Tax Provisions on Accounting Treatment of Financial Leases with Tax Realization as a Moderating Variable (Case Study at PT. Adira Dinamika Multi Finance Tbk) - Kirana Firda Maharani; Lili Syafitri; Aris Munandar (Majapahit Journal of Islamic Finance and Management, 2026)
This study aims to determine the influence provision taxation to treatment accountancy rent use business at PT. Adira Dinamika Multi Finance Tbk . Research data This obtained through distribution questionnaire to sample study that is PT. Adira employees Dinamika Multi Finance Tbk Palembang, which consisted of 95 respondents . Research data analysis techniques use PLS (Partial Least Squares ) technique that is processed with SmartPLS software version 3.2.9. Research results show that Provision Taxation influential positive and significant to Treatment Accountancy Lease at PT. Adira Multifinance Tbk , meanwhile Realization Tax No can moderate influence Provision Taxation to Treatment Accountancy Lease at PT. Adira Multifinance Tbk , which is proven with a negative T -statistic and a value significance on threshold 0.05.